Phylogenetic Footprinting Reveals Evolutionarily Conserved Regions of the Gonadotropin-Releasing Hormone Gene that Enhance Cell-Specific Expression - GIVENS, MARJORY L. (2004)
Reproductive function is controlled by the hypothalamic neuropeptide, GnRH, which serves as the central regulator of the hypothalamic-pituitary-gonadal axis. GnRH expression is limited to a small population of neurons in the hypothalamus. Targeting this minute population of neurons (as few as 800 in the mouse) requires regulatory elements upstream of the GnRH gene that remain to be fully characterized. Previously, we have identified an evolutionarily conserved promoter region (−173 to −1) and an enhancer (−1863 to −1571) in the rat gene that targets a subset of the GnRH neurons in vivo. In the present study, we used phylogenetic sequence comparison between human and rodents and analysis of the transcription factor clusters within conserved regions in an attempt to identify additional upstream regulatory elements. This approach led to the characterization of a new upstream enhancer that regulates expression of GnRH in a cell-specific manner. Within this upstream enhancer are nine binding sites for Octamer-binding transcription factor 1 (OCT1), known to be an important transcriptional regulator of GnRH gene expression. In addition, we have identified nuclear factor I (NF1) binding to multiple elements in the GnRH-regulatory regions, each in close proximity to OCT1. We show that OCT1 and NF1 physically and functionally interact. Moreover, the OCT1 and NF1 binding sites in the regulatory regions appear to be essential for appropriate GnRH gene expression. These findings indicate a role for this upstream enhancer and novel OCT1/NF1 complexes in neuron-restricted expression of the GnRH gene.